Method for manufacturing a silicon dioxide powder filler, the powder filler obtained therefrom, and the application thereof

KR103036683B1Active Publication Date: 2026-10-21ZHEJIANG THIRD AGE MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
KR1020237021071
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-31
Filing Date
2021-10-28
Publication Date
2026-10-21
Estimated Expiration
2041-10-28

Smart Images

  • Figure 112023068576663-PCT00001_ABST
    Figure 112023068576663-PCT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a silicon dioxide powder filler, wherein the manufacturing method comprises the steps of: dispersing a high dielectric constant powder in an aqueous solution and adding R1SiX3 to the aqueous solution to hydrolyze and condense to provide a polysiloxane powder, wherein the polysiloxane powder is a polysiloxane containing a T unit containing the high dielectric constant powder, and the particle size of the high dielectric constant powder is smaller than the particle size of the polysiloxane; and calcining the polysiloxane powder in an atmosphere containing oxygen, wherein the calcination temperature is within the range of 850°C to 1200°C, and obtaining a silicon dioxide powder filler containing the high dielectric constant powder inside. The present invention also provides a silicon dioxide powder filler obtained by the above manufacturing method and an application thereof. According to the method for manufacturing a silicon dioxide powder filler of the present invention, a silicon dioxide powder filler containing the high dielectric constant powder inside can be obtained, and through the high dielectric constant powder contained inside, it has a high dielectric constant and satisfies the requirements of a small-sized communication device.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to circuit boards and antenna packaging, and more specifically to a method for manufacturing a silicon dioxide powder filler, a powder filler obtained therefrom, and applications thereof. Background Technology

[0002] In the field of 5G communication, devices such as high-density interconnects (HDI), high-frequency high-speed boards, and circuit boards, including motherboards, must be assembled using radio frequency components. These circuit boards are generally composed of organic polymers such as epoxy resin, aromatic polyether, and fluoropolymer, as well as fillers; the fillers are primarily prismatic or spherical silicon dioxide, and their main function is to reduce the coefficient of thermal expansion of the organic polymers. Conventional fillers consist of spherical or prismatic silicon dioxide that are tightly packed and gradiented.

[0003] With the advancement of technology, communication devices are becoming increasingly smaller. Antennas, which are indispensable to communication devices, are also shrinking, leading to the use of packaged antenna AIPs. For design reasons, the substrates and packaging materials used to miniaturize antennas must possess high dielectric constant and low dielectric loss; however, existing known fillers cannot meet these requirements. The problem to be solved

[0004] To solve the problem that the dielectric constant of the filler known in the prior art does not meet the requirements of small-sized communication devices, the present invention provides a method for manufacturing a silicon dioxide powder filler, a powder filler obtained therefrom, and an application thereof. means of solving the problem

[0005] According to the method for manufacturing a silicon dioxide powder filler of the present invention, the manufacturing method comprises: dispersing a high dielectric constant powder in an aqueous solution and adding R1SiX3 to the aqueous solution to hydrolyze and condense to provide a polysiloxane powder, wherein the polysiloxane powder is a polysiloxane containing the high dielectric constant powder and containing a T unit, wherein R1 is a hydrogen atom or an organic group having 1 to 18 carbon atoms that can be independently selected, X is a group that can be decomposed by adding water, and the T unit is R1SiO3-, and the particle size of the high dielectric constant powder is smaller than the particle size of the polysiloxane; and a step S2 of obtaining a silicon dioxide powder filler containing the high dielectric constant powder inside, wherein the polysiloxane powder is calcined in an atmosphere containing oxygen, the calcination temperature is within the range of 850℃ to 1200℃.

[0006] Preferably, the particle size of the high dielectric constant powder is ≤ 1 / 3 of the particle size of the polysiloxane.

[0007] Preferably, R1SiX3 is methyltrimethoxysilane.

[0008] Preferably, the high dielectric constant powder is one or more selected from the group consisting of titanium oxide, zinc oxide, zirconium oxide, titanate, zincate, and zirconate. In a preferred embodiment, the high dielectric constant powder is barium titanate, titanium oxide, or calcium titanate.

[0009] Preferably, in step S1, the aqueous solution is a solution in which the main component is water. Preferably, the weight percentage of water in the aqueous solution is within the range of 80% to 100%. In a preferred embodiment, the aqueous solution is deionized water.

[0010] Preferably, the firing temperature is in the range of 850°C to 1100°C, and the firing time is in the range of 6 hours to 12 hours.

[0011] Preferably, the polysiloxane further comprises a Q unit, a D unit and / or an M unit, wherein the Q unit is SiO4-, the D unit is R2R3SiO2-, the M unit is R4R5R6SiO2-, and R2, R3, R4, R5 and R6 are each hydrogen atoms or independently selectable organic groups having 1 to 18 carbon atoms.

[0012] Preferably, the T unit raw material R1SiX3 of the polysiloxane is one or more selected from the group consisting of methyltrimethoxysilane, hydrocarbyltrihydrocarbyloxysilane, methyltrichlorosilane, and hydrocarbyltrichlorosilane, the Q unit raw material is one or more selected from the group consisting of tetrahydrocarbyloxysilane, silicon tetrachloride, and silicon dioxide, the D unit raw material is one or more selected from the group consisting of dihydrocarbyldihydrocarbyloxysilane and dihydrocarbyldichlorosilane, and the M unit raw material is trihydrocarbylhydrocarbyloxysilane, It is one or more selected from the group consisting of trihydrocarbylchlorosilane and hexahydrocarbyldisilazane. In a preferred embodiment, R1SiX3 silane is methyltrimethoxysilane, Q unit feedstock is tetraethoxysilane, and D unit feedstock is dimethyldichlorosilane.

[0013] Preferably, the polysiloxane is a spherical or angular polysiloxane.

[0014] Preferably, the manufacturing method further comprises the step of surface treating a silicon dioxide powder filler by adding a treatment agent, wherein the treatment agent comprises a silane coupling agent and / or disilazane; and the silane coupling agent is (R7) a (R8) b Si(M) 4-a-b And, R7 and R8 are independently selectable hydrocarbon groups having 1 to 18 carbon atoms, hydrogen atoms, or hydrocarbon groups having 1 to 18 carbon atoms substituted with functional groups, said functional groups are one or more selected from the group consisting of organic functional groups such as vinyl groups, allyl groups, styryl groups, epoxy groups, aliphatic amino groups, aromatic amino groups, methacryloxypropyl groups, acryloxypropyl groups, ureidopropyl groups, chloropropyl groups, mercaptopropyl groups, polysulfide groups, and isocyanatepropyl groups; M is an alkoxy group having 1 to 18 carbon atoms or a halogen atom, a = 0, 1, 2, or 3, b = 0, 1, 2, or 3, and a + b = 1, 2, or 3; said disilazane is (R9R 10 R 11 )SiNHSi(R 12 R 13 R 14 ) and, R9, R 10 , R 11 , R 12 , R 13 and R 14 is an independently selectable hydrocarbon group having 1 to 18 carbon atoms or a hydrogen atom.

[0015] The present invention also provides a silicon dioxide powder filler obtained by the above manufacturing method, wherein the silicon dioxide powder filler contains a high dielectric constant powder.

[0016] Preferably, the volume fraction of the high dielectric constant powder in the polysiloxane powder is in the range of 5% to 95%, and the average particle size of the silicon dioxide powder filler is in the range of 0.5 microns to 50 microns. In a preferred embodiment, the volume fraction of the high dielectric constant powder in the polysiloxane powder is in the range of 10% to 60%, and the average particle size of the silicon dioxide powder filler is in the range of 1.2 microns to 5.8 microns.

[0017] The present invention also provides applications for the silicon dioxide powder filler, wherein silicon dioxide powder fillers with different particle sizes are tightly packed into a resin and gradiented to form a composite material, which is applied to circuit board materials and semiconductor packaging materials.

[0018] Preferably, the application includes removing coarse particles of 1 micron, 3 micron, 5 micron, 10 micron, 20 micron or larger from silicon dioxide powder fillers using dry or wet sieving or inertial classification. Effects of the invention

[0019] According to the method for manufacturing a silicon dioxide powder filler of the present invention, a silicon dioxide powder filler containing a high dielectric constant powder inside can be obtained, and through the high dielectric constant powder contained inside, it has a high dielectric constant and satisfies the requirements of small-sized communication devices. In particular, since the high dielectric constant powder is coated inside the silicon dioxide, the inherent high surface activity performance and the characteristic of not being able to be coupled to a silane coupling agent do not affect the affinity between the silicon dioxide powder filler and the resin, and satisfy the requirements of circuit boards and antenna packaging. Brief explanation of the drawing

[0020] Figure 1 is a schematic diagram of a silicon dioxide powder filler according to Example 1 of the present invention. Figure 2 is a schematic diagram of a silicon dioxide powder filler according to Example 2 of the present invention. Figure 3 is a schematic diagram of a silicon dioxide powder filler according to Example 3 of the present invention. Specific details for implementing the invention

[0021] A preferred embodiment of the present invention is presented and described in detail with reference to the drawings attached below.

[0022] The detection method related to the following examples is,

[0023] Step of measuring the average particle size using HORIBA’s LA-700 laser particle size distribution analyzer; and

[0024] The process includes a step of determining the geometric structure of the powder by observing it with an electron microscope and analyzing it with EDX elements. Specifically, the powder and epoxy resin are mixed and cured. After slicing the cured product, the surface is polished, the cross-section of the polished particles is observed with an electron microscope, and the components of different regions are determined by EDX elemental analysis. The results are shown in a schematic diagram.

[0025] The volume fraction of high dielectric constant powder in polysiloxane powder is = (weight of high dielectric constant powder / specific gravity of high dielectric constant powder) / (weight of high dielectric constant powder / specific gravity of high dielectric constant powder + weight of polysiloxane / specific gravity of polysiloxane). The specific gravity of polymethylsiloxane (also called polymethylsilsesquioxane) is 1.34.

[0026] In the text, average particle size refers to the volume average diameter of the particles.

[0027] Example 1

[0028] A fixed weight portion of deionized water was taken at room temperature, and commercially available barium titanate with an average particle size of 0.3 microns was dispersed in the water. The mixture was placed in a reaction kettle equipped with a stirrer, stirring was started, and 80 weight portions of methyltrimethoxysilane were added and stirred for 1 hour. After the methyltrimethoxysilane was dissolved, 25 weight portions of 5% ammonia water were added and stirred for 10 seconds, after which stirring was stopped. After standing for 1 hour, the mixture was filtered and dried to obtain spherical powder. The powder was placed in a muffle furnace and the temperature was slowly raised to 1000°C while discharging organic matter in an oxygen-containing atmosphere. The mixture was then calcined for 6 hours to obtain spherical silicon dioxide powder containing barium titanate. The analysis results of the sample are listed in Table 1 below.

[0029] parts by weight of deionized water Average particle size (microns) Barium titanate volume fraction (%) Example 1 1100 1.2 10 Example 2 800 4.0 40 Example 3 600 5.8 60

[0030] The results of Examples 1 to 3 by electron microscopy and EDX analysis are as shown in FIG. 1, and barium titanate was coated on the inside of silicon dioxide.

[0031] Example 2

[0032] A fixed weight portion of deionized water was taken at room temperature, and commercially available titanium oxide with an average particle size of 0.38 microns was dispersed in the water. The mixture was placed in a reaction kettle equipped with a stirrer, and stirring was started. Then, 75 parts by weight of methyltrimethoxysilane and 5 parts by weight of tetraethoxysilane were added and stirred for 1 hour. After the methyltrimethoxysilane and tetraethoxysilane were dissolved, 25 parts by weight of 5% ammonia water were added and stirred for 10 seconds, after which stirring was stopped. After standing for 1 hour, the mixture was filtered and dried to obtain a powder. The powder was placed in a muffle furnace and the temperature was slowly raised to 850°C while discharging organic matter in an oxygen-containing atmosphere. The mixture was then calcined for 12 hours to obtain silicon dioxide powder containing titanium oxide. The analysis results of the sample are listed in Table 2 below.

[0033] parts by weight of deionized water Average particle size (microns) Volume fraction of titanium oxide (%) Example 4 1500 0.9 80

[0034] The results of Example 4 by electron microscopy and EDX analysis are as shown in Fig. 2, and titanium oxide was coated inside silicon dioxide.

[0035] Example 3

[0036] A fixed weight portion of deionized water was taken at room temperature, and commercially available calcium titanate with an average particle size of 2 microns was dispersed in the water. The mixture was placed in a reaction kettle equipped with a stirrer, stirring was started, and 78 parts by weight of methyltrichlorosilane and 2 parts by weight of dimethyldichlorosilane were added and stirred for 1 hour. The volume fraction of calcium titanate was 30%. The contents were filtered, washed with water, and dried. The white solid was ground using a grinder to obtain a prismatic powder with an average particle size of 50. The powder was placed in a muffle furnace, and the temperature was slowly raised to 1000°C while discharging organic matter in an oxygen-containing atmosphere. The mixture was then calcined for 12 hours to obtain the prismatic silicon dioxide powder containing calcium titanate of Example 5. The average particle size of the sample is 42 microns. As a result of electron microscopy and EDX analysis, the structure of Example 5 is as shown in Fig. 3.

[0037] It should be understood that the example samples obtained by Examples 1 to 5 above may undergo surface treatment. Specifically, they may be treated with vinyl silane coupling agents, epoxy silane coupling agents, disilazanes, etc., as needed. Additionally, one or more treatments may be performed as needed.

[0038] It should be understood that the above manufacturing method includes the step of removing coarse particles of 1, 3, 5, 10, 20 microns or larger from the filler using dry or wet sieving or inertial classification.

[0039] It must be understood that spherical silicon dioxide powder fillers of different particle sizes are tightly packed into the resin and gradiented to form a composite material.

[0040] The foregoing describes preferred embodiments of the present invention and is not intended to limit the scope of the invention; the embodiments of the present invention may also undergo various variations. Simple and equivalent variations and modifications made in accordance with the claims and specification of the application for the present invention are all within the scope of the claims of the present invention. Anything not described in detail in the present invention is of the ordinary technical nature.

Claims

Claim 1 A method for manufacturing a silicon dioxide powder filler, wherein the manufacturing method comprises: dispersing a high dielectric constant powder in an aqueous solution and adding R1SiX3 to the aqueous solution to hydrolyze and condense to provide a polysiloxane powder, wherein the polysiloxane powder is a polysiloxane containing the high dielectric constant powder and comprising a T unit, wherein R1 is a hydrogen atom or an organic group having 1 to 18 carbon atoms that is independently selectable, X is a group that can be decomposed by adding water, and the T unit is R1SiO3-, and the particle size of the high dielectric constant powder is smaller than the particle size of the polysiloxane; and a step S2 of calcining the polysiloxane powder in an atmosphere containing oxygen, wherein the calcination temperature is within the range of 850°C to 1200°C, and obtaining a silicon dioxide powder filler containing the high dielectric constant powder inside; and the manufacturing method further comprises a step of surface treating the silicon dioxide powder filler by adding a treatment agent, wherein the treatment agent comprises a silane coupling agent and / or disilazane; The above silane coupling agent is (R7) a (R8) b Si(M) 4-a-b And, R7 and R8 are independently selectable hydrocarbon groups having 1 to 18 carbon atoms, hydrogen atoms, or hydrocarbon groups having 1 to 18 carbon atoms substituted with functional groups, said functional groups are one or more selected from the group consisting of vinyl groups, allyl groups, styryl groups, epoxy groups, aliphatic amino groups, aromatic amino groups, methacryloxypropyl groups, acryloxypropyl groups, ureidopropyl groups, chloropropyl groups, mercaptopropyl groups, polysulfide groups, and isocyanatepropyl groups; M is an alkoxy group having 1 to 18 carbon atoms or a halogen atom, a = 0, 1, 2, or 3, b = 0, 1, 2, or 3, and a + b = 1, 2, or 3; said disilazane is (R9R 10 R 11 )SiNHSi(R 12 R 13 R 14 ) and, R9, R 10 , R 11 , R 12 , R 13 and R 14 A method for manufacturing a silicon dioxide powder filler characterized by being an independently selectable hydrocarbon group having 1 to 18 carbon atoms or a hydrogen atom. Claim 2 A method for manufacturing a silicon dioxide powder filler according to claim 1, characterized in that the particle size of the high dielectric constant powder is ≤ 1 / 3 of the particle size of the polysiloxane. Claim 3 A method for manufacturing a silicon dioxide powder filler according to claim 1, characterized in that the high dielectric constant powder is one or more selected from the group consisting of titanium oxide, zinc oxide, zirconium oxide, titanate, zincate, and zirconate. Claim 4 A method for manufacturing a silicon dioxide powder filler according to claim 1, characterized in that the calcination temperature is within the range of 850℃ to 1100℃ and the calcination time is within the range of 6 hours to 12 hours. Claim 5 A method for manufacturing a silicon dioxide powder filler according to claim 1, wherein the polysiloxane further comprises a Q unit, a D unit and / or an M unit, wherein the Q unit is SiO4-, the D unit is R2R3SiO2-, the M unit is R4R5R6SiO2-, and each of R2, R3, R4, R5 and R6 is a hydrogen atom or an organic group having 1 to 18 carbon atoms that can be independently selected. Claim 6 In claim 5, the T unit raw material R1SiX3 of the polysiloxane is one or more selected from the group consisting of methyltrimethoxysilane, hydrocarbyltrihydrocarbyloxysilane, methyltrichlorosilane, and hydrocarbyltrichlorosilane; the Q unit raw material is one or more selected from the group consisting of tetrahydrocarbyloxysilane, silicon tetrachloride, and silicon dioxide; the D unit raw material is one or more selected from the group consisting of dihydrocarbyldihydrocarbyloxysilane and dihydrocarbyldichlorosilane; and the M unit raw material is trihydrocarbylhydrocarbyloxysilane, A method for manufacturing a silicon dioxide powder filler characterized by being one or more selected from the group consisting of trihydrocarbylchlorosilane and hexahydrocarbyldisilazane. Claim 7 delete Claim 8 A silicon dioxide powder filler obtained by a manufacturing method according to any one of claims 1 to 6, characterized in that the silicon dioxide powder filler contains a high dielectric constant powder. Claim 9 A silicon dioxide powder filler according to claim 8, characterized in that the volume fraction of the high dielectric constant powder in the polysiloxane powder is within the range of 5% to 95%, and the average particle size of the silicon dioxide powder filler is within the range of 0.5 microns to 50 microns. Claim 10 delete Claim 11 delete

Citation Information

Patent Citations

  • Modified perovskite type composite oxide, manufacturing method thereof, and composite dielectric material

    KR1020110042184A